Implementasi Konsep Syirkah Al Amlak dalam Akad Al Musyarakah Al Muntahiyah Bi Al Tamlik (MMBT) pada Produk Pembiayaan Purchase Order (PO) Financing Fintech Syariah (Studi Kasus di PT Alami Fintek Sharia) - Fahmi, Zuel; Antonio, Muhammad Syafii; Rahman, Arip (Universitas Batanghari Jambi, 2024)
This research aims to understand the implementation of the syirkah al amlak concept in the al Musyarakah Al Muntahiyah Bi al Tamlik (MMBT) agreement on Sharia fintech purchase order (PO) financing products at PT Alami Fintek Sharia. The method used in this research is a qualitative method, based on a case study and interview approach, combining library research. The results of the research show that although the Fatwa of the National Sharia Council of the Indonesian Ulema Council (DSN-MUI) constructs the use of syirkah al 'inan in MMBT contracts, PT Alami Fintek Sharia prefers to apply syirkah al amlak which is permissible in fiqh, a process that is simpler and can be is a solution to murabahah financing which cannot be carried out, because the prospective recipient of the financing (beneficiary) is deemed to already own the goods, because they have made a transaction with the supplier (supplier) before applying for financing.